Geomorphic appraisal of landslides on the windward slope of Western Ghats, southern India - K. S. Sajinkumar and S. Anbazhagan (Nat Hazards, 2015)
The Western Ghats, the bold westerly escarpment of India paralleling the west coast, are characterized by different geologic and geomorphic units formed during different episodes of Earth’s history. The majority of these present day landforms evolved in response to the tectonic activity that the Western Ghats witnessed during the Tertiary period. The major structural features together with the geomorphic units have predominant role in the occurrence of cataclysmic landslides which the windward slope of Western Ghats witness during the peak monsoon season. The Kerala and Periyar lineaments, which are the sites of minor earthquakes, pass through the study area. Escarpments and structural hill systems are the vulnerable landforms for landslide occurrence. Due to the predominant role of these tectonic and geomorphic features in the capricious change of landforms, a study was carried out in this hilly terrain based on geomorphology. The study of soil, slope morphometry, relative relief, land use/land cover and hydrogeological conditions together with a multidimensional analysis in a GIS environment resulted in classifying the entire area into different landslide susceptible zones based on Bureau of Indian Standards. Moreover, the area is also divided into three zones based on the terrain conditions and the type of landslide occurrence. The methodology can well fit with any area experiencing the same terrain conditions and can be used to classify an area on the basis of landslide occurrence and geomorphology.